Superhydrophobic surfaces with fluorinated cellulose nanofiber assemblies for oil–water separation - Bashar, M. Mahbubul; Zhu, Huie; Yamamoto, Shunsuke; Mitsuishi, Masaya (RSC advances, 2017)
A Cellulose nanofiber (CNF) is an amazing nanomaterial produced from ubiquitous sources with outstanding mechanical, chemical, and barrier properties. This report describes facile functionalization of CNF with trichloro(1 H ,1 H ,2 H ,2 H -heptadecafluorodecyl)silane (THFS). The paste form CNF was solvent exchanged from initial water to AK-225 (a mixture of 3,3-dichloro-1,1,1,2,2-pentafluoropropane and 1,3-dichloro-1,1,2,2,3-pentafluoropuropane) before surface modification with THFS. The modified CNFs were dispersed uniformly in AK-225. The CNF film, which was prepared using simple drop casting, showed a superhydrophobic surface with a water contact angle of 160° and oleophilicity with a hexane contact angle of less than 35°. The modified CNF assembly is thermally stable, optically transparent and resistant to corrosive environment (acidic, basic and seawater solutions). The separation of oil and water mixtures was demonstrated using steel mesh coated with modified CNF. Separation efficiency greater than 99% was achieved by simple gravitational force for hydrocarbons and organic solvents. The as-prepared mesh can be used repeatedly more than 50 times with the same efficiency as the initial state.